CD5-Positive Intravascular Large B-Cell Lymphoma in a Patient with Wilson’s Disease: Case Report and Review of the Literature - Neha Gupta; Chrystalle Katte Carreon; Filiz Sen; Peter Farmer; Xinmin Zhang; Silvat Sheikh-Fayyaz; Nina Haghi (Case Reports in Pathology)
Intravascular large B-cell lymphoma (IVLBCL) is a rare extra-nodal B-cell lymphoma that proliferates within small/intermediate blood vessels and capillaries while sparing large blood vessels and organ parenchyma. Clinical presentation is highly variable and may include B symptoms, neurological deficits, and/or cutaneous findings. The diagnosis of IVLBCL is difficult due to multiorgan involvement and nonspecific symptoms. We describe the case of a 68-year-old male who presented with progressive weakness, confusion, and falls. He had a past medical history of liver cirrhosis secondary to Wilson’s disease. Physical exam and laboratory results revealed a lethargic man with jaundice, hepatic encephalopathy, and abnormal liver/kidney function tests. He expired after a short hospital course in the setting of hepatic and renal failure. Postmortem examination revealed large neoplastic lymphoid cells involving multiple organ blood vessels; however skin and neurologic involvement was absent. The neoplastic cells demonstrated B-cells positive for CD5, rendering a diagnosis of IVLBCL. Our case represents the occurrence of IVLBCL with CD5-positivity in a patient with Wilson’s disease, diagnosed at autopsy demonstrating the challenging nature of diagnosing IVLBCL.